2012
DOI: 10.1111/jfs.12001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Antibacterial Activity of Two Aromatic Herbs (Santolina chamaecyparissus and Sideritis angustifolia) Widely Used in the Folk Medicine

Abstract: The aim of this work was characterize the essentials oils (EOs) obtained from Santolina chamaecyparissus and Sideritis angustifolia determining (1) its chemical composition and (2) its effectiveness on the growth of some bacteria related to food spoilage, such as Listeria innocua, Serratia marcescens, Pseudomonas fragi, Pseudomonas fluorescens, Aeromonas hydrophila, Shewanella putrefaciens, Alcaligenes faecalis, Achromobacter denitrificans, Enterobacter amnigenus, Enterobacter gergoviae and Leuconostoc carnosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The chemical composition of the essential oils used in this work was previously determined by Ruiz-Navajas et al (30,31). In the T. moroderi EO, the main components were camphor (26.74%), 1,8-cineol (24.99%), myrcene (5.63%), and a-pinene (4.35%).…”
Section: Resultsmentioning
confidence: 91%
“…The chemical composition of the essential oils used in this work was previously determined by Ruiz-Navajas et al (30,31). In the T. moroderi EO, the main components were camphor (26.74%), 1,8-cineol (24.99%), myrcene (5.63%), and a-pinene (4.35%).…”
Section: Resultsmentioning
confidence: 91%
“…Santolina chamaecyparissus L. (S. chamecyparissus) is a well-known aromatic and medicinal plant that grows in North Africa and Southern Europe [1]. This plant has a strong aroma.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report of antibacterial activity of this species against S. saprophyticus. Most of the studies revealed that the essential oil of S. chamaecyparissus showed the highest antibacterial activity against different bacterial strains [18,49,50]. On the other hand, S. saprophyticus was resistant to the different concentrations of methanol plant extracts of A. judaica and F. carica L.…”
Section: Antibacterial Activitymentioning
confidence: 99%